Electrochemical Characterisation of Nano-Membrane Supported Liquid-Liquid Interfaces - Austen, Benjamin J. J. (Curtin University, 2022)
Electrochemical ion-transfer across miniaturised interfaces between immiscible electrolyte solutions (ITIES) is characterised by diffusion mass-transport limited currents. However, in the case of ion-transfer across nano-scale ITIES formed about porous silicon nitride (SiN) thin-films, it has been observed that the current usually exhibits a potential dependence. A review of existing work, physical and electrochemical characterisation, and theoretical discussion presented in this work provides new perspective on an enduring limitation of the promising SiN platform.